2021
DOI: 10.7554/elife.70055
|View full text |Cite
|
Sign up to set email alerts
|

Tissue environment, not ontogeny, defines murine intestinal intraepithelial T lymphocytes

Abstract: Tissue-resident intestinal intraepithelial T lymphocytes (T-IEL) patrol the gut and have important roles in regulating intestinal homeostasis. T-IEL include both induced T-IEL, derived from systemic antigen-experienced lymphocytes, and natural IEL, which are developmentally targeted to the intestine. While the processes driving T-IEL development have been elucidated, the precise roles of the different subsets and the processes driving activation and regulation of these cells remain unclear. To gain functional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…That IEL express granzymes constitutively at steady-state has been known for a long time, however the function of IEL-expressed Gzms is unknown. More than 80% of IEL express GzmA and GzmB, and previous proteomic analyses showed that IEL subsets express up to 20 million molecules of GzmA and ~5 million molecules of GzmB per cell (Brenes et al, 2021).…”
Section: Iel-derived Gzma/b Contribute To Intestinal Protection Against Infectionmentioning
confidence: 87%
See 2 more Smart Citations
“…That IEL express granzymes constitutively at steady-state has been known for a long time, however the function of IEL-expressed Gzms is unknown. More than 80% of IEL express GzmA and GzmB, and previous proteomic analyses showed that IEL subsets express up to 20 million molecules of GzmA and ~5 million molecules of GzmB per cell (Brenes et al, 2021).…”
Section: Iel-derived Gzma/b Contribute To Intestinal Protection Against Infectionmentioning
confidence: 87%
“…One subset of T lymphocytes that constitutively express GzmA and GzmB are intestinal intraepithelial T lymphocytes (IEL) (Brenes et al, 2021;Shires et al, 2001). IEL are a heterogenous population of T cells that occupy the intracellular space between intestinal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…KIR3DL3+ T cells in peripheral blood share many attributes with unconventional IELs, which have been described as having a "resting-but-activated" phenotype 95 . Innate-like CD8αα+ intraepithelial T cells are enriched for auto-reactive T cells, can be hyporesponsive to TCR engagement, are Vδ1-biased, rearrange TCR-α chains early in agonistic thymic selection, and upregulate NK cell inhibitory receptors and TCR-responsive genes 90,[95][96][97] . The transcriptional profile, cell surface receptor phenotype (CD3 low CD27 hi CD69+CD56+), and TCR repertoire of KIR3DL3-expressing T cells reflect these features.…”
Section: Discussionmentioning
confidence: 99%
“…4b). The dataset characterises the proteome of TCRαβ CD8αβ, TCRαβ CD8αα and TCRγd CD8αα T-IELS along with two conventional TCRαβ CD8αβ lymph node derived naïve CD8+ T cell populations, wild type (WT) and P14 21 . The raw files and MaxQuant output for this dataset are available in PRIDE with identifier PXD023140 22 , while the processed copy numbers are available in the ‘Downloads’ tab in ImmPRes.…”
Section: Data Recordsmentioning
confidence: 99%